PENGEMBANGAN DAYA TARIK WISATA DI AGROWISATA BALAI BENIH INDUK LUBUK MINTURUN PADANG - Yuliana Yuliana (JURNAL PENDIDIKAN DAN KELUARGA, 2017)
This research was motivated by the lack of tourist attraction in Agrowisata Balai Benih Induk (BBI) of Lubuk Minturun Padang, such as, there is no entertainment and recreation services at agro rides BBI, the least of the event activities in agrotourism meeting room BBI and the lack of souvenirs offered by agro tourism BBI Lubuk Minturun Padang. This research aims to determine the strategy of developing tourist attraction that has indicators in the form of tourist attractions, amenities and anchillary services are viewed from internal factors in the form of strengths and weaknesses and external factors in the form of opportunities and threats. This research is a descriptive research with qualitative data. Data collection technique is done by interview and observation that involves informant by using purposive sampling and snowball sampling technique. Development strategy of tourist attraction that can be done is in the form of: 1) Optimizing the function of land by developing tourism activities such as providing rides games and mini garden. 2) Develop MICE event in meeting and gazebo sessions such as holding workshops and agricultural exhibition. 3) Provide souvenirs by utilizing culture and network techniques.